Disney Channel tween programming : essays on shows from Lizzie McGuire to Andi Mack - Bell, Christopher E., 1974- (McFarland & Company, Inc., Publishers, 2020)
"Much has been written about the Walt Disney Company's productions, but the focus has largely been on animation and feature film created by Disney. In this essay collection, the attention is turned to The Disney Channel and the programs it presents for a largely tween audience. Since its emergence as a market category in the 1980s, the tween demographic has commanded purchasing power and cultural influence, and the impressionability and social development of the age group makes it an important range of people to study. Presenting both a groundbreaking view of The Disney Channel's programming by the numbers and a deep focus on many of the best-known programs and characters of the 2000s-shows like The Wizards of Waverly Place, That's So Raven and Hannah Montana-this collection asks the simple questions, "What does The Disney Channel Universe look and sound like? Who are the stories about? Who matters on The Disney Channel?" --